PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATA PELAJARAN PERAWATAN WAJAH BERJERAWAT DENGAN MENGGUNAKAN PENDEKATAN BERPIKIR KRITIS DI SMK NEGERI 1 SOOKO - Baharia Putri Kusuma; Biyan Yesi Wilujeng; Sri Usodoningtyas; Mutimmatul Faidah (Jurnal Tata Rias, 2024)
One of the ways in which teaching objectives have been achieved can be seen from the learning achievements achieved by students. Project Based Learning is an innovative, project-based, student-centered learning model. Critical thinking. Acne facial treatment is an action that is deliberately carried out for skin that has facial skin problems, including acne, oily facial skin, hyperpigmentation, and blackheads. This research aims to 1) the implementation of the learning model, 2) student learning outcomes, 3) students' ability to think critically, 4) student responses, with reference to data collection instruments 1) syntax implementation observation sheet, 2) student performance sheet, 3) critical thinking assessment sheet, 4) student response questionnaire sheet. The research used by researchers is a pre-experimental design research method using a one-shot case study research model using a quantitative approach. The subjects of this research were 29 grade 12 skin and hair beauty students who had received facial care material. The research results showed that 1) the implementation of learning syntax obtained an average of all aspects, namely 90% in the "very good" category, 2) the students' Psychomotor learning outcomes obtained an average of 82% and were categorized as "very competent", 3) the results of learning to think critical students obtained an overall average of 85% in the "very high" category, 4) student response questionnaires obtained an average of 82% in the "very good" category. Based on the research results, the application of the learning model is said to be feasible to apply to the learning process. Keywords: Learning models, critical thinking, acne facial care